Diagnostic Accuracy of the Oxygen Desaturation Index for Screening Severe Obstructive Sleep Apnea: Oxygen Desaturation Index for Screening Severe Obstructive Sleep Apnea - Malik, Muhammad Uzair Ijaz; Imran, Muhammad; Ali, Karamat; Rehman, Mehar; Ahmed, Sarfaraz; Malik, Muhammad Umair Ijaz (Pakistan Journal of Health Sciences, 2026)
Obstructive sleep apnea (OSA) is a common disorder with significant cardiovascular and metabolic effects. Although polysomnography-derived Aponea-Hypopnea Index (AHI) is the diagnostic gold standard, limited access has increased interest in simpler alternatives like Oxygen Desaturation Index (ODI). Objective: To determine the diagnostic accuracy of the ODI in identifying severe OSA compared with the AHI. Methods: This cross-sectional study was conducted at the Pulmonology department, Pak Emirates Military Hospital, from 01-03-2025 to 30-11-2025, including 126 patients with a STOP-BANG score>5. Overnight monitoring was performed for 4–8 hours using polysomnography with integrated pulse oximetry. ODI was calculated as a ≥3% drop in oxygen saturation lasting at least 10 seconds. All participants underwent polysomnography for AHI assessment. SPSS version 27.0 was used for analysis. Pearson correlation, linear weighted kappa measure, and ROC curve analysis were performed. Results: The patients’ mean age was 54.6 ± 11.9 years, and BMI was 34.1 ± 5.5 kg/m², predominantly male. Many patients had severe OSA. AHI and ODI showed a strong positive correlation with significant predictive value, and substantial agreement was observed between their severity classifications (κ=0.676, p<0.001). ROC analysis showed good diagnostic performance of ODI for identifying severe OSA (AUC=0.961, 95% CI: 0.932–0.990, p<0.001), with a sensitivity (94.3%) and specificity (79.5%) at an ODI cutoff ≥35. Conclusion: ODI shows a strong association with AHI and good accuracy for detecting severe OSA. It may be used as a non-invasive screening tool in resource-limited settings, but it cannot replace polysomnography.